A Programming System for Text-Editing Task Using Japanese Natural Language Text and Direct Manipulation - Kaneko, N.; Onisawa, T. (2006 IEEE International Conference on Systems, Man and Cybernetics, 2006)
In this paper, a programming system for text-editing task that uses both natural language text and direct manipulation is proposed. The system is based on the idea of programming by paraphrasing, which enables users with little knowledge of computer programming to make computer program by linguistic expressions because paraphrasing is usually used as human everyday language communication. The case-based reasoning (CBR) method is used for paraphrasing so that the system can acquire the meanings of unknown linguistic expressions from users. This paper also shows a running example using the system and the result of a subject experiment.